Robotic Intracorporeal Ileal Conduit Formation: Initial Experience from a Single UK Centre. (1st September 2013) - Bishop, Conrad V.; Vasdev, Nikhil; Boustead, Gregory; Adshead, James M.
Abstract : Objectives . To describe our technique of robotic intracorporeal ileal conduit formation (RICIC) during robotic-assisted radical cystectomy (RARC). To report our initial results of this new procedure. Patients and Methods . Seven male and one female patients underwent RARC with RICIC over a six-month period. Demographic, operative, and outcome data was collected prospectively. Median patient age was 75 years (range 62–78 years). Median followup was 9 months (range 7–14 months). Results . RARC with RICIC was performed successfully in all eight patients. The median total operating time was 360 minutes (range 310–440 minutes) with a median blood loss of 225 mL (range 50–1000 mL). The median length of stay was nine days (range 6–34 days). Four patients (50%) were discharged within seven days. Four patients (50%) experienced one or more complications. This included two Clavien I complications, two Clavien II complications, and two Clavien III complications. Two patients (25%) required transfusion of two units each. To date, there have been no complications associated with the ileal conduit. Conclusion . Whilst being technically challenging, this procedure is safe, feasible, and reproducible. Patients who avoid complication show potential for rapid recovery and early discharge.